2022
DOI: 10.3390/joitmc8010011
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Small- and Medium-Sized Enterprises’ Innovation and Resilience during COVID-19: The Tourism Sector

Abstract: Every day, companies are exposed to various risks arising from their environment, and small and medium enterprises (SMEs) are the most affected. This study emphasizes innovation and resilience as the starting points to understand how SMEs are influenced by external factors which are independent of the managers’ will. To date, we have seen several extreme factors that have conditioned businesses and entrepreneurs of these types of companies, such as the financial crisis of 2008. However, last year, in 2020, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 77 publications
0
26
1
1
Order By: Relevance
“…As a matter of fact, In the event of a microeconomic shock, it is possible for its effects to cascade throughout the entire economy, and have a significant aggregate impact on the economic performance of other businesses. Theoretical frameworks such as Turaev and Ganiev (2021), Wahyono and Hutahayan (2021), and Dias et al (2022) can be used to characterise mechanism of shock transmission and the scope of aggregate fluctuations as an economic propagation instrument in vulnerable economic situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a matter of fact, In the event of a microeconomic shock, it is possible for its effects to cascade throughout the entire economy, and have a significant aggregate impact on the economic performance of other businesses. Theoretical frameworks such as Turaev and Ganiev (2021), Wahyono and Hutahayan (2021), and Dias et al (2022) can be used to characterise mechanism of shock transmission and the scope of aggregate fluctuations as an economic propagation instrument in vulnerable economic situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In sum, it is necessary to deal with and investigate such subjects as innovation and resilience in line with perceiving the quality with which the external factors influence firms (Dias et al, 2022). Business entities with more innovative environments are more flexible in the face of the disorders because innovation, directly and indirectly, helps the firms corroborate the capabilities that per se positively influence the risk management competency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In high-volatility circumstances, organizations with low risk-takers may not perform at par (Shen et al, 2018). Dias et al (2022) found that resilient people increase their risk-taking ability with time in the tourism sector. As far as EP is concerned, it refers to the financial health of entrepreneurial ventures (Al .…”
Section: Risk-taking Propensitymentioning
confidence: 99%